Investigation Process Traffic Accident Offenders Of Minors The Police Resort Kebumen - Hari Condro Wibisono; Achmad Sulchan (Jurnal Daulat Hukum, 2019)
Often Traffic accidents occur in people's lives, even the culprit is Often a minor. This is due to lack of legal awareness and supervision from parents so that children are allowed to drive motorized vehicles before having a driver's license. As a knife of analysis, the theory of restorative justice and the theory of legal certainty are used. The results of the study Showed that the investigation process towards traffic accident underage perpetrators at the Kebumen Resort Police was in accordance with the provisions of the Criminal Procedure Code and Act Number 11 of 2012 concerning the Child Criminal Justice System. Factors causing traffic accidents with child offenders in the Kebumen Resort Police are dominated by human factors items, namely due to negative attitudes and behaviors of the Offender, Negligence (carelessness) in driving, lack of knowledge of the Offender in traffic and parents the perpetrators. Barriers to carrying out investigations into underage traffic accident perpetrators at the Kebumen Resort Police are suspects of fear during the examination even though they have been accompanied by parents and Bapas officers, the solution is by investigators to divert light questions along with the humor so as not to strain. In addition, It is also difficult, to ask permission from the school, Because if the permit is called by the police it will be a special note. Overcome The solution to this is to call there during school holidays. Barriers to carrying out investigations into underage traffic accident perpetrators at the Kebumen Resort Police are suspects of fear during the examination even though they have been accompanied by parents and Bapas officers, the solution is by investigators to divert light questions along with the humor so as not to strain. In addition, It is also difficult, to ask permission from the school, Because if the permit is called by the police it will be a special note. Overcome The solution to this is to call there during school holidays. Barriers to carrying out investigations into underage traffic accident perpetrators at the Kebumen Resort Police are suspects of fear during the examination even though they have been accompanied by parents and Bapas officers, the solution is by investigators to divert light questions along with the humor so as not to strain. In addition, It is also difficult, to ask permission from the school, Because if the permit is called by the police it will be a special note. Overcome The solution to this is to call there during school holidays.Keywords: investigation; traffic accident; children